2016
DOI: 10.1016/j.tra.2016.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Air transport and high-speed rail competition: Environmental implications and mitigation strategies

Abstract: We develop a duopoly model to analyse the environmental impact of high-speed rail (HSR) introduction in a market for travel served by air transport. We take into account the effects on the environment of induced demand, schedule frequency and HSR speed simultaneously, and we show that competition between the two modes may be detrimental to the environment depending on the magnitude of the pollution level of HSR relative to air transport. We conduct a simulation study based on the London-Paris market and we fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(36 citation statements)
references
References 58 publications
1
35
0
Order By: Relevance
“…In addition, D'Alfonso et al [39] studied the impact of air transport and HSR competition on the environment; they indicated that the introduction of HSR may have a net negative effect on the environment, since it may result in additional demand. Further, they conduct a simulation study based on the London-Paris market; it proved that HSR's introduction has increased LAP (the local air particular matter), but has decreased GHG (greenhouse gas) emissions [40].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, D'Alfonso et al [39] studied the impact of air transport and HSR competition on the environment; they indicated that the introduction of HSR may have a net negative effect on the environment, since it may result in additional demand. Further, they conduct a simulation study based on the London-Paris market; it proved that HSR's introduction has increased LAP (the local air particular matter), but has decreased GHG (greenhouse gas) emissions [40].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The availability of High Speed Train (HST) lines opens the possibility of partial substitution with short-haul and medium-haul intra-EU flights. HSR services, either through modal competition or through cooperation, already exist among EU airports like Frankfurt Main, Paris CDG, Madrid Barajas, and Amsterdam Schiphol, which are all connected to the Trans-European HSR Network [11]. Despite the current state of development, the potential of HSR is still not fully exploited.…”
Section: Journal Of Advanced Transportationmentioning
confidence: 99%
“…Although available literature agrees on the potential benefits of shifting air transport to rail, some authors argue that the introduction of new HSR services could have significant environmental impacts [15], mainly related to the medium and long-term impacts of the infrastructures realization, in terms of local biodiversity and habitats preservation [16]. D' Alfonso et al [11] modelled the environmental impacts of London-Paris HSR-air transport competition, capturing the effects of induced demand, schedule frequency, and HSR speed: the authors showed that the net environmental effects Journal of Advanced Transportation 3 can be negative since there is a negative trade-off due to the substitution effect.…”
Section: Journal Of Advanced Transportationmentioning
confidence: 99%
“…When considering the European case [20][21][22], a typical occupancy rate of 65% is deemed to be appropriate. According to available studies [23,24], a final specific energy consumption of HSR can be set in 0.057 kWh/pkm. With these assumptions as input, it is possible to calculate the specific emissions factor for the routes selected.…”
Section: Emissions For Rail Transportmentioning
confidence: 99%